ECONOMICAL DETERMINANTS OF DOMESTIC INVESTMENT - Al khatib, Hazem B.; Altaleb, Gassan S.; Alokor, Samer M. (European Scientific Journal, ESJ, 2012)
This study analyzes the trends of determinants of investments within the period (1980-2010) with focus on post-reform era efforts, both the short-run and long run movement of the investment process, using the co-integration econometrics method to estimate the dynamic of the variables in the study. This is in order to assess their behavior over time, and evaluate how these have either hindered or encouraged the growth of investment in the Jordanian economy.The results confirm previous results found in empirical literature. Namely, the growth rate GDP and exports and their significance in stimulating domestic investments. In addition to Foreign direct investment (FDI), and the development level of the financial sector and human capital in stimulating domestic investment only in the long-run. These results have implications for policy markets, investment prospectors, and foreign and domestic investors.